Canal Transportation and Centring Ratio of Paediatric vs Regular Files in Primary Teeth - Heba Abdelkafy; Alaa M. Eldehna; Nada A. Salem (Elsevier, 2023)
Background: During mechanical preparation of the primary root canal, the original anatomy of the tooth should be preserved and the instrument should be perfectly balanced centrally into the canal space for reducing the probability of canal transportation. The aim of this research was to compare canal transportation and canal centring ability in primary root canals using ProTaper Next (Dentsply Mailfair,), AF baby (Fanta), and Kidzo Elephant (Endostar, Poldent Sp.) files. Materials and methods: Eighteen root canals were randomly divided into 3 experimental groups (n = 6 in each group). Instrumentation was performed using ProTaper Next, Fanta AF baby, and Kidzo Elephant files in groups 1, 2, and 3, respectively. During the instrumentation procedure, the irrigation of 2 mL of 1.5% sodium hypochlorite between each file was done, followed by 5 mL of 17% ethylenediaminetetraacetic acid as a final irrigating solution. Cone-beam computed tomography images were obtained before and after instrumentation. Each group was evaluated for transportation and centring ratios. Results: On comparing all the tested groups within each root canal level canal transportation, the results revealed a statistically nonsignificant difference in the buccolingual direction (P > 0.05). Meanwhile, in the mesiodistal direction, group 1 showed a statistically highly significant difference compared to groups 2 and 3 at the cervical level (P < .01). However, in both middle and apical root canal levels, there was a statistically nonsignificant difference amongst all groups (P > 0.05). Regarding the centring ability comparison of the 3 groups within each root canal level, there was a statistically nonsignificant difference amongst all groups (P > 0.05) in both buccolingual and mesiodistal directions. Conclusions: The ProTaper Next regular rotary file and the paediatric rotary files showed no difference in canal transportation and centring ability in the buccolingual direction, while in the mesiodistal direction at the cervical root canal level, the ProTaper Next showed high transportation liability.